Not so sorry: abusers, false apologies, and the limits of forgiveness - Oakes, Kaya (Broadleaf Books, 2024)
"This book explores the history of Christian ideas of forgiveness and how our misunderstandings of forgiveness have contributed to patterns of clergy abuse, sexual violence and harassment, racial injustice, secrecy, and clericalism. The book examines trauma theory, narcissism, and other psychological aspects of forgiveness, as well as theological and sociological angles in our understanding of forgiveness. In her signature combination of history, first-person narrative, theology, reporting and analysis, Oakes brings these exploration to a wide audience, religious and secular, to provoke readers to new understandings of what forgiveness really means"--